KAJIAN KARAKTERISTIK LOKASI PEDAGANG KAKI LIMA (PKL) SEBAGAI BAGIAN DARI MANAJEMEN LINGKUNGAN PERKOTAAN DI SURABAYA - Sri Amiranti; Erwin Sudarma (Purifikasi, 2008)
The existence of the street vendor (PKL) in Surabaya evidently emerges urban environmental problem, i.e. traffic jam, and environmental dirtiness. The incompatibility of location with the city spatial order and the negative environmental impact, has pushed the local government to remove the location to other place. These relocation efforts were failed evidently, indicated by the return of the street vendor to the formerly location or moving to other location. The reason is: the new location is not suitable for the street vendor’s activity. In order to determine the most suitable location for this street vendor, a characterization of the street vendor location being considered as “the correct location” for this informal sector activities, is needed. Behavior setting approach will be used to reveal the synomorphy between activity and the place. Results of the characterization of street vendor location study can be used as a basic determinant for street vendor location selection, as a part of urban environmental management